Postpartum Family Planning Use and Its Determinants among Women of the Reproductive Age Group in Low-Income Countries of Sub-Saharan Africa: A Systematic Review and Meta-Analysis - Yemane, Tesfalem Tilahun; Bogale, Getahun Gebre; Egata, Gudina; Tefera, Tilahun Kassa (International Journal of Reproductive Medicine, 2021)
Background. Postpartum family planning is the initiation and use of family planning services within the first 12 months following childbirth. Postpartum contraceptives reduce maternal and infant mortality by preventing unplanned and unwanted pregnancies and by spacing pregnancies at least two years after the previous birth. Thus, it is usually designed as an integral part of reproductive and maternal and child health programs. Therefore, the aim of this systematic review and meta-analysis is to estimate the pooled prevalence of postpartum modern contraceptive use and identify its determinants in low-income countries of sub-Saharan Africa. Methods. A systematic review and meta-analysis of published and unpublished studies were used. PubMed, HINARI, ScienceDirect, Cochrane Library, Wiley Library, ETH Library, and Google Scholar were used to search all articles. STATA 14 software was used for data analysis. Funnel plots and Egger’s test were used to examine the risk of publication bias. Heterogeneity was checked by using Cochran’s Q test and I2 test. A random effect model was computed to estimate the pooled prevalence. Results. A total of 33 articles were included. The pooled prevalence of postpartum contraceptive use in low-income countries of sub-Saharan Africa was 37.41%, 95% CI: (31.35, 43.48%). Secondary and above level of education (AOR 2.09, 95% CI: (1.52, 2.86)), discussion with husband (AOR 3.68, 95% CI: (1.96, 6.89)), resumption of menses (AOR: 3.98, 95% CI: (2.62, 6.03)), ANC follow-up (AOR; 5.10, 95% CI: (3.57, 7.29)), knowledge of modern family planning (AOR: 5.65, 95% CI: 3.58, 8.93)), and family planning counseling during ANC (AOR =5.92, 95% CI: (2.54, 13.79)) were found to be determinants of postpartum contraceptive utilization. Conclusion. In this systematic review and meta-analysis, the prevalence of postpartum modern contraceptive use was found to be low compared to the existing global recommendations. Therefore, empowering maternal education, delivering adequate counseling, and strengthening existing integrated maternal and child health services are highly recommended to increase postpartum contraceptive use. This trial is registered with CRD42020160612.